Implementasi Pemasaran IndiBiz oleh Pegawai Telkom Indonesia Witel Yogyakarta terhadap Kesadaran (Awareness) dan Penggunaan Layanan oleh UMKM - Fadhilah, Irfan; Fadhilla, Hanifa Nur (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the implementation of the IndiBiz marketing strategy carried out by PT Telkom Indonesia through the Telkom Witel Yogyakarta unit and its influence on awareness, perception, and decision to use services by micro, small, and medium enterprises (MSMEs). The study uses a mixed methods approach that combines quantitative and qualitative methods. The quantitative approach was carried out through a survey by distributing questionnaires to MSMEs who are the target of IndiBiz marketing in the Yogyakarta area. The data obtained were analyzed using descriptive analysis, validity and reliability tests, and multiple linear regression analysis. The results of the study indicate that the implementation of the IndiBiz marketing strategy has a positive and significant influence on the level of MSME awareness of the service. A high level of awareness is also proven to influence MSMEs' decisions in using IndiBiz services.